Insulin Oversecretion in MSG-Obese Rats is Related to Alterations in Cholinergic Muscarinic Receptor Subtypes in Pancreatic Islets - Rosiane A. Miranda; Aryane R. Agostinho; Isis H. Trevenzoli; Luiz F. Barella; Claudinéia C. S. Franco; Amanda B. Trombini; Ananda Malta; Clarice Gravena; Rosana Torrezan; Paulo C. F. Mathias; Júlio C. de Oliveira (Cellular Physiology and Biochemistry, 2014)
Background/ Aims: Impaired pancreatic beta cell function and insulin secretion/action are a link between obesity and type 2 diabetes, which are worldwide public health burdens. We aimed to characterize the muscarinic acetylcholine receptor (mAChR) M1-M4 subtypes in isolated pancreatic islets from pre-diabetic obese rats that had been treated neonatally with monosodium L-glutamate (MSG). Methods: At 90 days of age, both the MSG and the control groups underwent biometric and biochemical evaluation. Anti-muscarinic drugs were used to study mAChR function either in vivo or in vitro. Results: The results demonstrated that atropine treatment reduced insulin secretion in the MSG-treated and control groups, whereas treatment with an M2mAChR-selective antagonist increased secretion. Moreover, the insulinostatic effect of an M3mAChR-selective antagonist was significantly higher in the MSG-treated group. M1mAChR and M3mAChR expression was increased in the MSG-obese group by 55% and 73%, respectively. In contrast, M2mAChR expression decreased by 25% in the MSG group, whereas M4mAChR expression was unchanged. Conclusions: Functional changes in and altered content of the mAChR (M1-M4) subtypes are pivotal to the demand for high pancreatic beta cell insulin secretion in MSG-obese rats, which is directly associated with vagal hyperactivity and peripheral insulin resistance.